Analysis of replication, cell division-mediated spread, and HBV envelope protein-dependent pseudotyping of three mammalian delta-like agents - Gnouamozi, Gnimah Eva; Zhang, Zhenfeng; Prasad, Vibhu; Lauber, Chris; Seitz, Stefan; Urban, Stephan (Viruses, 2024)
The human hepatitis delta virus (HDV) is a satellite RNA virus that depends on hepatitis B virus (HBV) surface proteins (HBsAg) to assemble into infectious virions targeting the same organ (liver) as HBV. Until recently, the evolutionary origin of HDV remained largely unknown. The application of bioinformatics on whole sequence databases lead to discoveries of HDV-like agents (DLA) and shed light on HDV's evolution, expanding our understanding of HDV biology. DLA were identified in heterogeneous groups of vertebrates and invertebrates, highlighting that the evolution of HDV, represented by eight distinct genotypes, is broader and more complex than previously foreseen. In this study, we focused on the characterization of three mammalian DLA discovered in woodchuck (Marmota monax), white-tailed deer (Odocoileus virginianus), and lesser dog-like bat (Peropteryx macrotis) in terms of replication, cell-type permissiveness, and spreading pathways. We generated replication-competent constructs expressing 1.1-fold over-length antigenomic RNA of each DLA. Replication was initiated by transfecting the cDNAs into human (HuH7, HeLa, HEK293T, A549) and non-human (Vero E6, CHO, PaKi, LMH) cell lines. Upon transfection and replication establishment, none of the DLA expressed a large delta antigen. A cell division-mediated viral amplification assay demonstrated the capability of non-human DLA to replicate and propagate in hepatic and non-hepatic tissues, without the requirement of envelope proteins from a helper virus. Remarkably L-HDAg but not S-HDAg from HDV can artificially mediate envelopment of WoDV and DeDV ribonucleoproteins (RNPs) by HBsAg to form infectious particles, as demonstrated by co-transfection of HuH7 cells with the respective DLA expression constructs and a plasmid encoding HBV envelope proteins. These chimeric viruses are sensitive to HDV entry inhibitors and allow synchronized infections for comparative replication studies. Our results provide a more detailed understanding of the molecular biology, evolution, and virus-host interaction of this unique group of animal viroid-like agents in relation to HDV.
Gesehen am 06.02.2025